Lament as Prophetic Ritual of Eschatological Hope: Reading Jephthah’s Daughter in Scripture and Liturgy - Lopez, JoAnn Melina (Lumen et Vita, 2015)
The story of Jephthah’s daughter in Judges 11 is brief but gruesome, one of the “texts of terror” which haunt the depiction of women in scripture. Jephthah, a war hero, vows to sacrifice whoever comes out to meet him from his house upon his return in exchange for God’s assistance in a skirmish with an invading army. To his horror, and ours, it is his only child, a young girl, who greets him on his return, and he is committed to continuing with his sacrifice. Unlike with other mentions of child sacrifice in the scriptures, Jephthah’s daughter is not delivered from her fate by the intervention of God or human action. Instead the young woman, nameless in the scriptures, gathers her female companions around her to mourn before her death, and is mourned by all the women of Israel, who gather annually to mark her death. This paper will examine the narrative of Jephthah’s daughter in scripture, alongside a critique of her presentation and interpretation in the lectionary of the Catholic Church. The ways in which the Church engages with violent scripture texts, especially in our public liturgical action, speaks to the cogence of our proclamation of hope in a world in which texts of terror continue to be inscribed upon the bodies of women and children. The focus of the paper will be the prophetic lament of Jephthah’s daughter, her companions, and the generations of women after them, which I argue should be reclaimed and connected with the prophetic and eschatological hope of the Eucharist when this scripture is proclaimed in liturgy.